2013
DOI: 10.3109/00016357.2013.822098
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of monolithic all-ceramic crowns made of high translucent yttrium oxide-stabilized zirconium dioxide compared to porcelain-veneered crowns and lithium disilicate crowns

Abstract: Objective The aim of the study was to provide data on the fracture strength and fracture mode of monolithic high translucent Y-TZP crowns and porcelainveneered high translucent Y-TZP crown cores and to compare that data with the fracture strength and fracture mode of porcelain-veneered Y-TZP crown cores and monolithic lithium disilicate glass-ceramic crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
130
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 37 publications
10
130
0
19
Order By: Relevance
“…Johansson et al reported that translucent TZP shows high strength, supporting the results of this study 27) . The fact that the Zpex specimens showed the same level of strength as conventional TZ3YB suggests that Zpex can be used clinically.…”
Section: Monolithic Tzpssupporting
confidence: 82%
See 1 more Smart Citation
“…Johansson et al reported that translucent TZP shows high strength, supporting the results of this study 27) . The fact that the Zpex specimens showed the same level of strength as conventional TZ3YB suggests that Zpex can be used clinically.…”
Section: Monolithic Tzpssupporting
confidence: 82%
“…Ting et al reported that a TZP of 1.0 mm thickness showed the same level of fracture load as metal-ceramic crowns 31) . Johansson et al reported that the fracture load of a TZP crown with an occlusal surface thickness of 1.8 mm was 2,700 N or more 27) . Furthermore, under the biaxial flexural test in this study, the fracture load of 1.0 mm-thick translucent TZP can estimate the 600 N that is equivalent value of the average biaxial flexural strength of the same TZP with 1,060 MPa.…”
Section: Monolithic Tzpsmentioning
confidence: 99%
“…This could affect the mechanical properties of the new material. However, few studies have analyzed possible differences in strength between high-translucent and low-translucent Y-TZP, and even fewer have compared these materials with glass-ceramics (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic crowns offer other advantages such as reduced production time and improved cost-effectiveness (9). Crown preparation always involves a risk, causing preparation trauma to the vital tooth, a risk that is increased the more extensive the preparation is (10).…”
Section: Introductionmentioning
confidence: 99%
“…Because crown preparation involves traumatization to the vital tooth, eliminating the veneering material in monolithic crowns allows to achieve minimally invasive preparations and subsequent restorations [49][50][51].…”
Section: Simulation Methods Applied In Monolithic Ceramic Crownsmentioning
confidence: 99%